Technological challenges Faced by Pedagogy and Education Sciences students during the COVID-19 pandemic (Educational Knowledge, 2023)
The COVID-19 pandemic has reshaped higher education worldwide. This article highlights the technological challenges encountered by pedagogy and education sciences students at a public university in Honduras. The qualitative descriptive study employs focus group discussions involving eight university students. Results indicate limitations in teacher-student and peer interaction when using virtual environments. Additionally, connectivity issues pose a challenge in this new teaching modality. However, student resilience has facilitated autonomous learning during this transformative educational process.
Keywords: Higher Education; Technology; Pedagogy; Pandemic; Honduras